Power spectral analysis of heart rate variability in drug naive essential hypertension: Comparison between two antihypertensive drugs - Sultana, Shamima; Begum, Shelina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2025)
Background: Autonomic imbalance is associated with drug naïve essential hypertension and antihypertensive drugs may improve autonomic balance. Losartan and amlodipine are two different drug of choice to treat essential hypertension. Power spectral analysis of heart rate variability (HRV) is an important marker for detecting autonomic balance. Objective: To compare the effect of losartan and amlodipine on autonomic balance in essential hypertensive patients. Method: This longitudinal study enrolled 120 drug naive male hypertensive patients (age 30-55 years) from the Out Patients Department of Cardiology, BSMMU, Dhaka. Sixty apparently healthy normotensive male subjects with similar age were control. Patients were divided into two equal groups. One group received daily oral dose of 50 mg losartan and other group 5 mg amlodipine. Autonomic balance was assessed by power spectral analysis of Heart Rate Variability (HRV) and HRV data were recorded by a polyrite D. HRV of the patients were measured at baseline, after 3 months, and 6 months of medication. For statistical analysis ANOVA, independent sample ‘t’ test and paired sample ‘t’ were performed. Result: High frequency normalized units (HFn.u), total power (TP) were significantly lower (P<0.001) and low frequency normalized unit (LF n.u), LF/HF ratio were significantly higher (P<0.001) in all patients compared to control at baseline. In both drug groups HF n.u and total power significantly increased(P<0.001) whereas LF n.u and LF/ HF ratio were found significantly decreased(P<0.001) after 3 months of treatment compared to their baseline values. After 6 month treatment data demonstrated further significantly increased (p<0.05) HF n.u and total power compared to their values of 3 months treatment. But these values were found significantly higher in losartan treated patients compared to amlodipine group. Conclusion: The result concluded that autonomic balance was improved by both drugs but losartan was more potent. J Bangladesh Soc Physiol 2024;19(2): 82-88